Cochlear and Vestibular Volumes in Inner Ear Malformations. Issue 8 (September 2022) - Breitsprecher, Tabita M.; Pscheidl, Alexander; Bächinger, David; Volkenstein, Stefan; Dhanasingh, Anandhan; Van Rompaey, Vincent; Mlynski, Robert; Dazert, Stefan; Van de Heyning, Paul; Langner, Sönke; Roland, Peter; Weiss, Nora M.
Objective: A "gold standard" for quantitatively diagnosing inner ear malformations (IEMs) and a consensus on normative measurements are lacking. Reference ranges and cutoff values of inner ear dimensions may add in distinguishing IEM types. This study evaluates the volumes of the cochlea and vestibular system in different types of IEM. Study Design: Retrospective cohort. Setting: Tertiary academic center. Patients: High-resolution CT scans of 115 temporal bones (70 with IEM; cochlear hypoplasia [CH]; n = 19), incomplete partition (IP) Types I and III (n = 16), IP Type II with an enlarged vestibular aqueduct (Mondini malformation; n = 16), enlarged vestibular aqueduct syndrome (n = 19), and 45 controls. Interventions: Volumetry by software-based, semiautomatic segmentation, and 3D reconstruction. Main Outcome Measures: Differences in volumes among IEM and between IEM types and controls; interrater reliability. Results: Compared with controls (mean volume, 78.0 mm 3 ), only CH showed a significantly different cochlear volume (mean volume, 30.2 mm 3 ; p < 0.0001) among all types of IEM. A cutoff value of 60 mm 3 separated 100% of CH cases from controls. Compared with controls, significantly larger vestibular system volumes were found in Mondini malformation (mean difference, 22.9 mm 3 ; p = 0.009) and IP (mean difference, 24.1 mm 3 ; p = 0.005). In contrast, CH showed a significantly smaller vestibular system volume (mean difference, 41.1 mm 3 ; p < 0.0001). A good interrater reliability was found for all three-dimensional measurements (ICC = 0.86–0.91). Conclusion: Quantitative reference values for IEM obtained in this study were in line with existing qualitative diagnostic characteristics. A cutoff value less than 60 mm 3 may indicate an abnormally small cochlea. Normal reference values for volumes of the cochlea and vestibular system may aid in diagnosing IEM.